Preoperative and Postoperative, Three-dimensional Gait Analysis in Surgically Treated Patients With High-grade Spondylolisthesis. Issue 2 (February 2021) - Trivedi, Jayesh; Srinivas, Shreya; Trivedi, Rishi; Davidson, Neil; Munigangaiah, Sudarshan; Bruce, Colin; Bass, Alf; Wright, David
Abstract : Background: High-grade spondylolisthesis (HGS) (Myerding grade III-V) in adolescents can lead to a marked alteration of gait pattern and maybe the presenting symptom in these patients. This characteristic gait pattern in patients with HGS has been referred to as the "pelvic waddle." Modern 3-dimensional (3D) gait analysis serves an important tool to objectively analyze the different components of this characteristic gait preoperatively and postoperatively and is an objective measure of postoperative improvement. This study demonstrates the use of 3D gait analysis preoperatively and postoperatively in a cohort of 4 consecutive patients with HGS treated surgically at a single tertiary referral center and utilize this to objectively evaluate outcome of surgical treatment in these patients. This has not been reported previously in a cohort of patients. Methods: This is a prospective analysis of patients with HGS who underwent surgical intervention for spondylolisthesis at a single institution. Patient demographics, clinical, and radiologic assessment were recorded, and all patients underwent 3D gait analysis before and after surgical intervention. Kinetic, kinematic, and spatial parameters were recorded preoperatively and postoperatively for all patients. This allowed the outcome of change in gait deviation index, before and after surgical treatment, to be evaluated. Results: We were able to review complete records of 4 adolescent patients who underwent surgical treatment for HGS. Mean age at surgery was 13.5 years with a minimum follow-up of 2.5 years postoperatively (average 40 mo). Preoperative gait analysis revealed marked posterior pelvic tilt in 2 patients, reduced hip and knee extension in all 4 patients and external foot progression in 3 of the 4 patients. Along with an observed improvement in gait, there was an objective improvement in gait parameters postoperatively in all 4 patients. Gait deviation index score improved significantly from 78.9 to 101.3 (mean). Conclusions: Preoperative gait abnormalities exist in HGS and can be objectively analyzed with gait analysis. Surgical intervention may successfully resolve these gait abnormalities and gait analysis is a useful tool to assess the outcome of surgery and quantify an otherwise intangible benefit of surgical intervention. Level of Evidence: Level IV—case series.